Actualization of Student's Role in Answering the Direction of National Political Policy: Questioning Food Self-Support in the Environment Reviewing from Social Welfare - Muhammad Dwi Prasetyo; Yogi Syahputra Al Idrus (Jurnal Multidisiplin Madani, 2023)
Everything that is processed or not processed with the aim of being used as food or as a drink for individual consumption which includes raw materials or food additives or other materials and in this case through a process of making, processing, or preparing food. or drinks and derived from biological a product in agriculture, this is the definition of food. The existence of an in-depth understanding for students who in this case have a role as agents of change to be pro-active towards the government and play a role in the food sector is the purpose of writing this paper. In this case, the problems related to food self-sufficiency are answered by the existence of Law no. 18 of 2012, the empirical normative method with a legal basis and environmental conditions as an analytical tool was chosen by the author to describe the discussion in this journal. So from that this journal focuses on 1) Reconstructing the role of students in increasing food self-sufficiency and 2) The idea of  the role of students in increasing food self-sufficiency